Neighbourhood walkability and physical activity: moderating role of a physical activity intervention in overweight and obese older adults with metabolic syndrome. (20th November 2020) - Colom, Antoni; Mavoa, Suzanne; Ruiz, Maurici; Wärnberg, Julia; Muncunill, Josep; Konieczna, Jadwiga; Vich, Guillem; Barón-López, Francisco Javier; Fitó, Montserrat; Salas-Salvadó, Jordi; Romaguera, Dora
Abstract: Background: While urban built environments might promote active ageing, an infrequently studied question is how the neighbourhood walkability modulates physical activity changes during a physical activity intervention programme in older adults. We assessed the influence of objectively assessed neighbourhood walkability on the change in physical activity during the intervention programme used in the ongoing PREvención con DIeta MEDiterránea (PREDIMED)-Plus trial. Method: The present study involved 228 PREDIMED-Plus senior participants aged between 55 and 75, recruited in Palma de Mallorca (Spain). Overweight/obese older adults with metabolic syndrome were randomised to an intensive weight-loss lifestyle intervention or a control group. A walkability index (residential density, land use mix, intersections density) was calculated using geographic information systems (1 km sausage-network buffer). Physical activity was assessed using accelerometer and a validated questionnaire, at baseline and two follow-up visits (6-months and 1-year later). Generalised additive mixed models were fitted to estimate the association between the neighbourhood walkability index and changes in physical activity during follow-up. Results: Higher neighbourhood walkability (1 z-score increment) was associated with moderate-to-vigorous accelerometer assessed physical activity duration, ( β  = 3.44; 95% CI = 0.52; 6.36 min/day). When analyses were stratified by intervention arm, the association was only observed in the intervention group ( β  = 6.357; 95% CI = 2.07;10.64 min/day) ( P for interaction = 0.055). Conclusions: The results indicate that the walkability of the neighbourhood could support a physical activity intervention, helping to maintain or increase older adults' physical activity.